Paroxysmal Cold Hemoglobinuria in an Adult with Respiratory Syncytial Virus - Leibrandt, Ryan; Angelino, Kenneth; Vizel-Schwartz, Monique; Shapira, Ilan (Case Reports in Hematology, 2018)
Paroxysmal cold hemoglobinuria (PCH) is a rare form of cold autoimmune hemolytic anemia first discovered in the early 20th century in adults with tertiary syphilis. Today, it is more commonly seen in children as a life-threatening anemia during a viral upper respiratory tract infection (URI). Although respiratory syncytial virus (RSV) has previously been reported to cause PCH in a child, herein we present the first documented case in an adult. The Donath–Landsteiner (DL) test, the diagnostic test for PCH, was positive on two separate occasions. The patient was treated successfully with warming and avoidance of cold temperatures. To facilitate identification of this rare entity by clinicians, we include a discussion about the pathophysiology, diagnosis, and treatment of PCH.